Technical Efficiency of High-Technology Industries in the Crisis: Evidence from Russia; Journal of the Knowledge Economy; Vol. XX - Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Vukovic D. Darko; Spitsina (Spitsyna) L. Yu. Lubov Yurievna (2022, 2022)
Title screen